The Role of Dr. Saddeeq Atroshi in Kurdish Political Movement - Othman, Khalil M. (Humanities Journal of University of Zakho, 2015)
The Kurdish history is full of big and famous names of Kurdish politicians and intellectuals who have left imprints on the various walks of life that they were engaged in. Dr Siddeeq Atroshi is one of those personalities who had a prominent role in the political movement during the period under study. Beyond politics, this figure had a significant part in the administrative, scientific and cultural are nasin Iraq, which does indicate the high standing he had, from early 1940s to mid-1960s of the 20th century. Dr Siddeeq Atroshi engaged, directly or indirectly, in forming most of the political associations, clubs and parties that emerged at the time. Dr Atroshi magnificently served the Kurdish cause from several aspects. He emphasized the demands of the Kurdish liberation movement in the field of education; logically resolved the partisan differences between the Kurdistan Democratic Party and the Iraqi Communist Party; he tried to unite and organize the Kurdish Home and solve the outstanding issues between the Kurdish parties (sides). Dr Atroshi spent most of his life in Baghdad until the Coup 1963 and afterwards he fled to Kurdistan and settled in the areas liberated by the Peshmerga and run by the Kurds.